Abdul Aziz bin Saud's foreign policy and its impact on the establishment of representation The diplomatic mission of Saudi Arabia and the justifications for the need for advisors (2091-2091) (Journal of the College of Basic Education, 2022)
Abdul Aziz bin Abdul Rahman bin Al Saud lived through the conditions his country went through since his birth in 1880